Is Ockham’s razor losing its edge? New perspectives on the principle of model parsimony - Marina Dubova; Suyog Chandramouli; Gerd Gigerenzer; Peter Grünwald; William Holmes; Tania Lombrozo; Marco Marelli; Sebastian Musslick; Bruno Nicenboim; Lauren N. Ross; Richard Shiffrin; Martha White; et al. (Proceedings of the National Academy of Sciences, 2025)
The preference for simple explanations, known as the parsimony principle, has long guided the development of scientific theories, hypotheses, and models. Yet recent years have seen a number of successes in employing highly complex models for scientific inquiry (e.g., for 3D protein folding or climate forecasting). In this paper, we reexamine the parsimony principle in light of these scientific and technological advancements. We review recent developments, including the surprising benefits of modeling with more parameters than data, the increasing appreciation of the context-sensitivity of data and misspecification of scientific models, and the development of new modeling tools. By integrating these insights, we reassess the utility of parsimony as a proxy for desirable model traits, such as predictive accuracy, interpretability, effectiveness in guiding new research, and resource efficiency. We conclude that more complex models are sometimes essential for scientific progress, and discuss the ways in which parsimony and complexity can play complementary roles in scientific modeling practice.